Exploring the statistical fragility of creativity studies using the alternate uses task: A systematic review protocol - Vikram Arora; Alex Thabane; Adam Sutoski; Kim Madden; Mohit Bhandari (PLoS ONE, 2025)
Introduction The Alternate Uses Task (AUT), where participants generate multiple novel uses for everyday objects, is one of the most widely used measures of creative potential. While many creativity studies report statistically significant effects on AUT outcomes, the robustness of these findings has not been systematically evaluated. Given concerns about over-reliance on p-values and the risk of fragile results, this systematic review aims to assess the statistical fragility of AUT-based findings using the continuous fragility index (CFI). Methods This protocol has been registered in Open Science Framework (DOI: 10.17605/OSF.IO/KFQGU). Eligible studies will include two-arm experimental designs (randomized or non-randomized) that report statistically significant between-group differences on AUT outcomes. We plan to conduct a comprehensive search of databases, including Medline, Embase, PsycInfo, and ERIC, up to July 21, 2025. Two reviewers will independently screen studies and perform data extraction. The primary outcome will be the median CFI across included studies, calculated using a simulation-based method developed for continuous outcomes. As a secondary objective, we plan to conduct a multivariable linear regression and subgroup analyses to explore study-level predictors of fragility. Dissemination We will disseminate results through publication in a peer-reviewed journal and presentations at academic conferences. The findings aim to raise awareness of statistical fragility in creativity research and encourage stronger reporting and methodological practices for studies using the AUT.